2014
DOI: 10.1098/rspb.2013.3011
|View full text |Cite
|
Sign up to set email alerts
|

Visual navigation in starfish: first evidence for the use of vision and eyes in starfish

Abstract: Most known starfish species possess a compound eye at the tip of each arm, which, except for the lack of true optics, resembles an arthropod compound eye. Although these compound eyes have been known for about two centuries, no visually guided behaviour has ever been directly associated with their presence. There are indications that they are involved in negative phototaxis but this may also be governed by extraocular photoreceptors. Here, we show that the eyes of the coral-reef-associated starfish Linckia lae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 34 publications
6
71
0
Order By: Relevance
“…In addition, we found that visual information was heavily filtered by the eye, enabling the animals to see large, dark, inanimate objects, like coral boulders, against a blue background best. The methods used in this study and the results obtained closely resemble those of a previous study (Garm and Nilsson 2014) on L. laevigata.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In addition, we found that visual information was heavily filtered by the eye, enabling the animals to see large, dark, inanimate objects, like coral boulders, against a blue background best. The methods used in this study and the results obtained closely resemble those of a previous study (Garm and Nilsson 2014) on L. laevigata.…”
Section: Discussionsupporting
confidence: 77%
“…8) and would be easiest to detect visually by starfish. As found in L. laevigata, the measured spectral sensitivity curve was narrower than the opsin template (Garm and Nilsson 2014). It could be that the damaging ultraviolet rays are filtered out by the eye, thereby narrowing the spectral sensitivity curve at the blue end of the spectrum (O'Connor et al 2010b).…”
Section: Properties Of the Visual Systemmentioning
confidence: 89%
See 3 more Smart Citations